0402 Does lung cancer incidence and mortality differ with the type of asbestos fibre? : evidence from western australia. (21st August 2017) - Sodhi, Nita; deKlerk, Nick; Franklin, Peter; Brims, Fraser; Peters, Susan; Olsen, Nola; Musk, Bill
Abstract : Background: Crocidolite is known to be the most carcinogenic form of asbestos for mesothelioma. This study aimed to assess if there was a difference between crocidolite and mixed asbestos fibre exposure for rates of lung cancer incidence and mortality after adjusting for smoking. Methods: Administrative datasets were used to identify lung cancer incidence and deaths in three Western Australian cohorts of people exposed to: crocidolite as miners and millers at Wittenoom; crocidolite as residents of Wittenoom; and mixed asbestos fibres occupationally. Multivariable Poisson regression models were used to compare the 5 year incidence and mortality rates between these cohorts after starting a health surveillance program. Explanatory variables included radiological evidence of asbestosis and cumulative asbestos exposures as determined through our Asbestos Job-Exposure Matrix (AsbJEM) after adjusting for smoking pack years, time since smoking cessation, age and sex. Results: The 5 year lung cancer incidence (n=176) and mortality (n=125) rates increased with radiological evidence of asbestosis (2.4-fold), increasing cumulative asbestos exposure and smoking pack-years. Compared with crocidolite miners and millers, Wittenoom ex-residents had the lowest rates (Incidence Rate Ratio (RR): 0.31, 95% CI: 0.15–0.67; and Mortality RR: 0.39 95% CI: 0.17–0.88). However, there were no significant differences identified between people occupationally exposed to mixed asbestos fibres (Incidence Rate Ratio (RR): 0.92, 95% CI: 0.61–1.39; and Mortality RR: 1.07 95% CI: 0.66–1.73) and Wittenoom workers. Conclusion: Mixed asbestos fibre exposure seems to be an equally potent cause of lung cancer as crocidolite after adjusting for smoking history.